PENGARUH LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANISATIONAL CITYZHENSHIP BEHAVIOR KARYAWAN PADA PT INDOMART KECAMATAN SELAPARANG - Muhammad Hidayat; Zainal Abidin; Rusminah Hs (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2021)
ABSTRACT This research entitled The Effects of Work Environment and Organizational Commitment on Organizational Citizenship Behavior at PT. Indomaret, Selaparang Sub-District, Mataram Municipality aimed at finding out the effects of each variable of Work Environment and Organizational Commitment on Organizational Citizenship Behavior and the most dominant variable towards Organizational Citizenship Behavior. The type of this research was associative research. The method of data gathering was census. The number of populations in this research was 63 people. The types of data used in this research were quantitative and qualitative. The analysis used in this research was multiple linear regression consisted of F-test, t-test and R2 test. Prior to the tests, instrument quality test was conducted consisted of validity test and reliability test as well as classic assumption test consisted of normality test and multicollinearity test. Regarding t-test, it showed that Work Environment and Organizational Commitment had positive and significant effects on Organizational Citizenship Behavior while the variable having the dominant effect was work environment. R2 test showed that the effect of independent variables (work environment and organizational commitment) towards dependent variable (organizational citizenship behavior) was 0.511 or 51.1%.